Mobilisasi Masyarakat sebagai Guardiant of Tranparency: Strategi Pencegahan Korupsi dalam Pengelolaan Investasi Danantara - Herianto Setiawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The rise in corruption cases in Indonesia significantly hampers investment, impacts national economic growth, and undermines the integrity of public institutions. This study highlights the strategic role of public mobilization as guardians of transparency in preventing potential corruption at the Danantara Investment Management Agency (BPI). Using a normative legal research approach enriched by qualitative analysis of the regulatory framework and best practices, this study examines the legal basis supporting public participation and formulates an effective corruption prevention strategy in the digital era. The results show that optimizing the role of the public through information transparency and the use of information and communication technology (ICT) plays a crucial role in building accountability and detecting irregularities. Access to audit data, financial evaluations, and public information is an important instrument in strengthening oversight. The use of ICT allows the public to analyze anomalous patterns, assess institutional performance, and provide constructive feedback on investment management policies. However, this mobilization faces significant challenges. First, the complexity of financial and regulatory data often makes it difficult for the general public to interpret. Second, limited digital literacy hinders the public's ability to utilize oversight technology. Third, the urgent need for certainty of legal protection for whistleblowers or oversight participants is a determining factor in the success of the mobilization. Therefore, strengthening regulations that guarantee legal protection, increasing digital literacy capacity, and developing user-friendly public oversight platforms are necessary. Synergy between the government, investment management institutions, and the public is key to creating a transparent, responsive, and adaptive oversight system to technological developments. This way, the active role of the public can be optimized to strengthen the integrity of BPI Danantara and promote a healthy investment climate in Indonesia.